Stereotip dan Kompetensi Komunikasi Bisnis Antarbudaya Bali dan Cina (Studi Di Kalangan Pengusaha Perak Bali Dan Cina) - Lestari, Puji (FISIP Universitas Atma Jaya Yogyakarta, 2007)
Abstract The result of this disertation made them capable Gudykunst and Kim’s intercultural theory, Spitzberg’s competence model of intercultural business communication, and ethnocentrism theory. There are agree with intercultural business communication reality in the community of Balinese and Chinese silver industrialists. The result of SEM statistical testing indicates that culture (for instance cultural values), socio-culture (for instance interethnic experience) and psycho-culture (for instance social prejudice) formed the interethnic stereotype that may influence the intercultural business communication competence. The results also approved that intercultural business communication competence is formed by motivation, knowledge and skill of communications in accordance with Spitzberg’s model. It indicates that ethnocentrism attitude toward other ethnic is not categorized as high but still exist.